understanding the determinant factors of chronic disease behaviour among Malaysian low-income workers: an integrated model approach - Abu Bakar, Azrin Shah; Abdul Rahman, Haliza; Mohd Nazan, Ahmad Iqmer Nashriq; Kadir Shahar, Hayati (Human Resource Management Academic Research Society, 2022)
Chronic disease is a public health concern all around the world including Malaysia. It is reported to be increasing and becoming one of the major problems among the community. This issue, however, is poorly understood among low-income groups. The identifications of factors associated with chronic disease management behaviour are necessary as the strategies to reduce the prevalence of chronic disease and increase the quality of life and wellbeing among the unfortunate. Therefore, this study aims to understand chronic disease management behaviour among this vulnerable population. This paper illuminates the prospects via the literature overviews limitations that indicate the needs for an integrated model to identify factors influencing chronic disease management behaviour among lowincome workers in Malaysia. Guided by an integrating of Theory of Reasoned Action (TRA) and Socio Ecological Model were used to understand chronic disease management behaviors among low-income workers. Hence, this paper provides important insights about the determinants of chronic disease management behaviour among Malaysian low-income workers and proposes an integrated model with the hope of looking into driving testable hypotheses to provide empirical evidence.